EU After COVID-19: An Opportunity for Policy Coordination - Antonia Díaz; Luis A. Puch (Intereconomics)
Abstract Despite all the difficulties inherent to our political organisation, the European Union has taken a bold step by doubling the EU budget for the next six years with the NGEU fund.